Blau syndrome with hypertension and hepatic granulomas: a case report and literature review - Yao, Fangling; Tan, Bei; Wu, Di; Shen, Min (Frontiers in Pediatrics, 2023)
Background: Blau syndrome (BS) is a monogenic disorder caused by NOD2 gene variants characterized by the triad of granulomatous polyarthritis, rash, and uveitis. Atypical symptoms were recognized in one-third to one-half of individuals with BS. The objective of this study is to describe the clinical features of BS patients with hypertension and digestive system involvement.The complete clinical data of a BS patient complicated with hypertension and hepatic granulomas were collected and documented. We also performed a literature search to find out all reported cases of BS with hypertension and digestive system involvement.We reported a 19-year-old man presented with early onset symmetric polyarthritis and hypertension at age 5, hepatic granulomas and cirrhosis at age 19. He was diagnosed as BS by the finding of a variant in the NOD2 gene (R334W). Through literature review, 24 patients with BS have been reported to have hypertension and 38 patients have different digestive system manifestations such as hepatic granulomas, hepatosplenomegaly, diverticulitis and intestinal granuloma. Among 38 BS patients with digestive system involvement, 14 had hepatic granulomas proven by liver biopsy.Conclusions: Hypertension and digestive system involvement are rare manifestations of BS.Clinicians especially rheumatologists need to be aware of atypical symptoms of BS.